Marine Origin vs. Synthesized Compounds: In Silico Screening for a Potential Drug Against SARS-CoV-2 - Amar Osmanović; Mirsada Salihović; Elma Veljović; Lamija Hindija; Mirha Pazalja; Maja Malenica; Aida Selmanagić; Selma Špirtović-Halilović (Scientia Pharmaceutica)
Although COVID-19 is not a pandemic anymore, the virus frequently mutates, resulting in new strains and presenting global public health challenges. The lack of oral antiviral drugs makes it difficult to treat him, which makes the creation of broadly acting antivirals necessary to fight current and next epidemics of viruses. Using the molecular docking approach, 118 compounds derived from marine organisms and 92 previously synthesized compounds were screened to assess their binding affinity for the main protease and papain-like protease enzymes of SARS-CoV-2. The best candidates from the xanthene, benzoxazole, and coumarin classes were identified. Marine-derived compounds showed slightly better potential as enzyme inhibitors, though the binding affinities of synthesized compounds were similar, with the best candidates displaying affinity values between 0.2 and 0.4 mM. Xanthenes, among both marine origin and synthesized compounds, emerged as the most promising scaffolds for further research as inhibitors. The papain-like protease was found to be more druggable than the main protease. Additionally, all top candidates met the criteria for various drug-likeness properties, indicating good oral bioavailability and low risk of adverse effects. This research provides valuable insights into the comparative affinities of marine origin and synthesized compounds from the xanthene, coumarin, and benzoxazole classes, highlighting promising candidates for further in vitro and in vivo studies.